Binky takes charge - Spires, Ashley, 1978- (Spires, Ashley, 1978- Binky adventure., 2012)
"Binky the space cat has been promoted to lieutenant. He's now in charge of training the next generation of space cadets. But then he meets the new space kitten -- who isn't a kitten at all! Is someone trying to pull the fur over his eyes? Binky and Captain Gracie need to figure out the new cadet before the next alien attack!"--Information from Amazon.com.